To the question of differentiation of ataxias (analytical review) - T. V. Myronenko; M. O. Myronenko; S. A. Fedorkovsky (Вестник медицинского института «Реавиз»: Реабилитация, врач и здоровье, 2022)
Based on the analysis of numerous studies, the authors summarized the current understanding of the problem of cerebellar ataxia. Issues related to the cause of the development of coordinating disorders, pathophysiological mechanisms of their occurrence, depending on trigger factors, are consistently covered. The features of the clinical course of acquired and congenital ataxias are systematized, their differential diagnostic differences are presented. Methods for diagnosing cerebellar ataxia are highlighted, diagnostic information content of laboratory, genetic, instrumental research methods is shown. The main directions of drug and non-drug methods of treatment of cerebellar ataxia are considered, their effectiveness is given. The main principles of rehabilitation of this group of patients are formulated.